The Invisible Crisis: Framing the Remediation of Milwaukee's Lead Laterals - (:unkn) unknown (My University, 2018)
When Milwaukee’s municipal water system was developed in 1874, one-half-inch lead pipes were used to convey water from the mains in the street to a customer’s home; the City has since acknowledged that nearly 100,000 such lead pipes are still in use today, a revelation which has opened for debate whether or not these pipes pose a galvanizing public health risk with far-reaching policy and infrastructure implications. This study explores the community response to Milwaukee’s lead laterals through the efforts of the Freshwater for Life Action Coalition (FLAC). How do Milwaukeeans understand the risks posed by the lead laterals? In what ways do they believe themselves, the City of Milwaukee, or other actors to be responsible for remediating these risks? How has FLAC framed the issue to energize their local social activist movement? Even more so, is there some about lead, specifically, which makes it difficult to organize a movement? How does lead itself play a role in understanding risk and responsibility in this social movement? By exploring the factors that contribute to how Milwaukeeans understand the risks posed by the lead pipes, this study seeks to understand in what ways — if at all — they consider themselves and the City to be responsible for remediating those risks.
Keywords: Activism; Collective-action frames; Lead; Milwaukee; Non-humans; Social movements